Repair of central venous access devices in intestinal failure patients is safe and cost-effective: A retrospective single centre cohort study. Issue 6 (June 2021) - Fletcher, Jane; Woodham, Diane; Cooper, Sheldon C.
Summary: Introduction: Patients with chronic intestinal failure (IF) require home parenteral nutrition (HPN). Central venous access is needed for prolonged use of PN, usually via a long term central venous access device (CVAD). Post insertion there may be mechanical complications with a CVAD such as catheter rupture or tear. Repair of damaged CVADs is possible to avoid risks associated with catheter replacement in patients with IF. However, catheter related blood stream infections (CRBSI) are a concern when CVAD's are accessed or manipulated. Aims: To investigate the success of repair of CVADs in patients with IF on HPN, related to repair longevity and incidence of CRBSI following repair. Method: Nutrition team records of CVAD repairs carried out in patients with IF were reviewed retrospectively for the period April 2015 to March 2019. Results: Nutrition Clinical Nurse Specialists carried out 38 repairs in 27 patients. Male n  = 5, female n  = 22; mean age 55 years. Catheter longevity before first repair ( n  = 27): median 851 days, IQR 137–1484 days. 30/38 (78.9%) of repairs were successful lasting ≥30days. Hospital admission was avoided in 76% of cases. 4 patients in the failed repair group underwent catheter re-insertion where 4 had a further, subsequently successful, repair, an overall success rate of 89.4% (34/38). 30-day CRBSI rate was 0.09/1000 catheter days in repaired catheters. In comparing costs, there is a potential cost saving of 2766GBP for repair compared to replacement of damaged CVADs. Conclusion: Repair of tunnelled CVADs in patients with IF is successful and safe with no increased risk of CRBSI. Significant cost savings may be made.